Moral and Psychological Features of the Motivational Sphere of Juveniles who Commit Crimes: Risk Assessment of Determining Communication - Yuzikova, Nataliіa; Korniakova, Tatiana; Khomiachenko, Svitlana; Chasova, Tetiana (European Journal of Sustainable Development, 2021)
The purpose of this research is the identification of moral and psychological features of the motivational sphere of juvenile offenders (delinquents) and identification of risks in the process of socialization of juveniles that have a determining connection with the illegal (deviant) behavior of the child. The article presents the results of empirical studies of the specifics of the motivational sphere of juvenile offenders; the assessment of the risks caused by the weakening of the socializing role of family institutions, education, and upbringing is submitted. In addition, the statistical analysis of the moral and psychological characteristics of juveniles serving a sentence associated with imprisonment compared to a control group of peers who are not in conflict with the law is given.